Attribute-based access to distributed data over P2P networks. (13th November 2007) - Agrawal, Divyakant; El Abbadi, Amr; Suri, Subhash
Peer-to-Peer (P2P) networks are distributed data sharing systems with no dedicated and centralised infrastructure. While P2P systems have been used so far mainly for file sharing, their true potential lies as a vast, loosely connected worldwide infrastructure for sharing resources, data and information. This paper addresses a natural step in the evolution of P2P: data and information sharing where data is accessed based on its attributes or properties. We have identified diverse applications that can benefit directly from attribute-based access to distributed data over P2P systems. Based on the application requirements, we propose three new models for both data distribution and data accesses.